TEKNIK ANALISIS DALAM KOMPONEN PEMBELAJARAN - Dolong, Jufri (Inspiratif Pendidikan, 2016)
The relevance of the learning component is the appropriateness and suitability of the relationship between the parts in the mental and physical process done by teachers and learners to achieve the objectives stated. In learning process, there are eight interrelated components and complement each other to achieve the objectives. Moreover, the relevance of the learning component also suggests the importance of each component. The learning will not be able to run if one of the components is not met. Then, learning component is a system being linked to one another and interacts in the learning development. The relevance components with other components can be viewed during the formulation of the goal itself in which the teachers formulate the goal. In this case, teacher is an educator who is also one of the components in learning. In addition, students also have a strong relevance to the objectives in which the educators set goals. Then, the consideration is the students’ behavior and characteristics.